2021
DOI: 10.7831/ras.9.0_195
|View full text |Cite
|
Sign up to set email alerts
|

Various Methods for Controlling the <i>Bakanae</i> Disease in Rice

Abstract: Bakanae disease, caused by Fusarium fujikuroi, is a serious problem in rice production. This disease is widespread across the world and leads to substantial yield losses. F. fujikuroi is known to produce various secondary metabolites, including the plant hormone gibberellin, which induces typical bakanae symptoms. In this article, authors overviewed the methods for controlling bakanae disease, including the use of host resistance, chemical compounds, biocontrol agents, natural products, and physical methods. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…Gupta et al [8] revealed that some strains of Trichoderma, Pseudomonas, and Bacillus have anti-fungal effects against bakanae disease. A similar finding was investigated by Jing and Suga [17]. Therefore, the introduction of biocontrol agents may be an innovative treatment capable of suppressing bakanae disease to be used instead of chemical treatment.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Gupta et al [8] revealed that some strains of Trichoderma, Pseudomonas, and Bacillus have anti-fungal effects against bakanae disease. A similar finding was investigated by Jing and Suga [17]. Therefore, the introduction of biocontrol agents may be an innovative treatment capable of suppressing bakanae disease to be used instead of chemical treatment.…”
Section: Discussionsupporting
confidence: 78%
“…Among them, P. fluorescens, B. cereus, and Trichoderma spp. isolates have an excellent potential to be used as biocontrol agents of F. fujikuroi in rice [16,17]. The capacity of these organisms to colonize roots and their beneficial interactions with plants can lead to an efficient defense against the disease, since they can trigger host defense responses against Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%